LILRB4 signalling in leukaemia cells mediates T cell suppression and tumour infiltration. (25th October 2018) - Deng, Mi; Gui, Xun; Kim, Jaehyup; Xie, Li; Chen, Weina; Li, Zunling; He, Licai; Chen, Yuanzhi; Chen, Heyu; Luo, Weiguang; Lu, Zhigang; Xie, Jingjing; et al.
Abstract Immune checkpoint blockade therapy has been successful in treating some types of cancer but has not shown clinical benefits for treating leukaemia1 . This result suggests that leukaemia uses unique mechanisms to evade this therapy. Certain immune inhibitory receptors that are expressed by normal immune cells are also present on leukaemia cells. Whether these receptors can initiate immune-related primary signalling in tumour cells remains unknown. Here we use mouse models and human cells to show that LILRB4, an immunoreceptor tyrosine-based inhibition motif-containing receptor and a marker of monocytic leukaemia, supports tumour cell infiltration into tissues and suppresses T cell activity via a signalling pathway that involves APOE, LILRB4, SHP-2, uPAR and ARG1 in acute myeloid leukaemia (AML) cells. Deletion ofLILRB4 or the use of antibodies to block LILRB4 signalling impeded AML development. Thus, LILRB4 orchestrates tumour invasion pathways in monocytic leukaemia cells by creating an immunosuppressive microenvironment. LILRB4 represents a compelling target for the treatment of monocytic AML. The receptor LILRB4 on monocytic leukaemia cells suppresses T cell activity and support the infiltration of tumour cells into tissues.